(untitled) (Journal of Contemporary Issues in Accounting, 2026)
The study examined the vitality of Forensic Audit practice in the public sector of the South East Nigeria towards the effective detection cum deterrence of fraud in Ministries, Departments and Agencies in the region. To achieve the stated broad objectives, The study specifically ascertained the effect of forensic arbitration skills on fraud deterrence in Ministries, Departments and Agencies in South-East, Nigeria. Furthermore, it investigated the effect of forensic litigation skills on fraud deterrence in Ministries, Departments and Agencies in South-East, Nigeria. Deploying the survey research design, a total of 260 Respondents was determined using Yaro Yamanene formula and sampled in MDAs in the 5 States namely Anambra, Abia, Ebonyi, Enugu, and Imo States which constitute the South East region of Nigeria. A 5-point rating scale well articulated google form-based research e-questionnaire served as the channel for the harvest of opinion from the Respondents. The Multiple regression analytical technique was used to test the relevant hypotheses, and the study found that arbitration skills have a significant and positive effect on fraud deterrence in the public sector in South East Nigeria (coefficient 0.268; pivalue 0.0000). It was also discovered that forensic litigation skills significantly and positively affect fraud deterrence in MDAs (coefficient 0.257; p-value 0.0000). The study therefore concludes that Ministries, Departments, and Agencies (MDAs) equipped with forensic expertise are more capable of identifying irregularities, disrupting potential fraudulent schemes, and creating operational climates that discourage unethical financial practices. As result, it recommends that the Head of the Civil Service of the Federation need to develop and institutionalize a continuous professional development program focused on forensic arbitration for internal auditors and legal officers in MDAs. Also, the Attorney-General of the State need to establish specialized forensic litigation desks within all public sector legal departments to facilitate proactive legal responses to fraud, including case preparation, evidence preservation, and collaboration with forensic auditors for deterrent prosecution.